Postmodern discrediting the figures of the Author and the Reader in the novel “Kys” by T. Tolstaya - Казаков, Ігор Миколайович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The article deals with the way the figures of Author and Reader are represented in the plot of the novel “Kys” by T. Tolstaya. The discreditation of the figures is proved to have the features of postmodernist literature. In the novel events which are narrated about, occurred after atomic Explosion, which thrown off humanity in cultural and social evolution to late Stone Age. In this future exists race named “golubchiki” – mutants who were born after Explosion and who are spiritual degraded. The main character is Benedict. He rewrites texts allegedly written by the chief of represented society – Fedor Kuzmich Kablukov. Benedict is trying to interpret the written in his own way, which brings to birth of Reader, turning according to post-modernism into new “Dieu cache”. However Benedict’s intellection as the most “golubchiks” is primitive. The character invariably compares what is read to his own experience, his associations are concretely ignorant and remain within the framework of native environment. But Benedict himself fully believes in post-modern way that he is Reader, standing above Author. Demonstrative is also Benedict’s perception of Pushkin : he does not see in Pushkin anything sacral or mythological. In his opinion the poet is nothing but a common wooden statuette, engraved therewith by himself. So, Benedict is not the admirer but ingenuous maker, the creator of Pushkin, in other words, a God for his creation. There is also another “author” in the novel – Fedor Kuzmich, who takes the advantage of the situation when Author dies (all true authors have died before or after an Explosion). Kablukov recopies somebody else’s text zealously. Thereby usurping Author’s role, being only the typical scripter indeed, who have replaced the author in post-modern study. Accordingly, in the novel “Kys” already on the plotline level is designed post-modern situation of author’s death: all literary texts are written very long ago, in the modernity of “golubchiks” is nothing new created; the only “author” – Fedor Kuzmich appears to be just a scripter, who recopies another’s compositions. Author’s figure in that way turns into figment and is almost completely leveled. In “Kys” is also disconsidered the meaning of born Reader, who imagined himself Dieu cache, though he is not capable making any adequate interpretation of a text.